Asked by priyankmalukar | 8th Sep, 2009, 10:55: PM

Expert Answer:


To prove OB = OC we need to prove that ODB OEC


Since DOB = COE ......(1)

and DBO = ECO  .......(2)

Now in DBC and EBC

ODB = OEC        (By cpct)

 ABC = ACB         (sides of an isoceles triangle)

BC is common

DBCEBC     (AAS congruency)

BD = EC .......(3)

DC = EC  

ODB OEC           (from 1,2,3)

⇒ OB = OC

Similarly do the (ii) part.

In case you get stuck post each query individually.



Answered by  | 9th Sep, 2009, 09:05: AM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.